2019
DOI: 10.14512/gaia.28.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Who should waste less? Food waste prevention and rebound effects in the context of theSustainable Development Goals

Abstract: The issue of food waste prevention plays a role in global and national policies. Such prevention can reap economic and, in particular, environmental benefits. As our study shows, these environmental benefits are often lost due to indirect rebound effects. Income differences play a crucial role here.Addressing food waste prevention is one target of the Sustainable Development Goals (SDGs) and a major task for the UN Environmental Programme and the European Commission. It is promising in terms of its environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Thus, besides the reduction of the aforementioned market intervention measures and the integration of specific measures to reduce food waste into the new CAP regulations, increased prices for food products in accordance with their environmental impact would raise the appreciation of food and thus also stimulate the avoidance of food waste. This also implies an abolishment of environmental harmful subsidies [14,77,81,86,112,113]. Additionally, food waste could be an incorporated indicator in the fitness-check assessment of the CAP (for a CAP fitness-check see [86]).…”
Section: The Common Agricultural Policy and The Common Fisheries Policymentioning
confidence: 99%
“…Thus, besides the reduction of the aforementioned market intervention measures and the integration of specific measures to reduce food waste into the new CAP regulations, increased prices for food products in accordance with their environmental impact would raise the appreciation of food and thus also stimulate the avoidance of food waste. This also implies an abolishment of environmental harmful subsidies [14,77,81,86,112,113]. Additionally, food waste could be an incorporated indicator in the fitness-check assessment of the CAP (for a CAP fitness-check see [86]).…”
Section: The Common Agricultural Policy and The Common Fisheries Policymentioning
confidence: 99%
“…Food waste reduction was identified as a key issue in foodservices and the broader food system, with one-third of all food wasted, which equates to 1.3 billion tonnes per year globally. 5,7 Within the studies included in this review, numerous food waste reduction strategies were incorporated that were customised to suit individual foodservice establishments, albeit the majority being in a university setting. Although infrastructure and policies supporting or mandating waste management practices are generally a local/regional issue, all foodservice establishments can adopt waste management processes within the hierarchy of recycling and waste management.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review identified 33 studies that included a wide range of environmentally sustainable strategies. Food waste reduction was identified as a key issue in foodservices and the broader food system, with one‐third of all food wasted, which equates to 1.3 billion tonnes per year globally 5,7 . Within the studies included in this review, numerous food waste reduction strategies were incorporated that were customised to suit individual foodservice establishments, albeit the majority being in a university setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations